(untitled) (Journal of Medical Sciences, 2022)
Chronic HCV infection contributed with the development of some diseases such as liver cirrhosis, cancer, and liver failure especially in HIV-positive patients during active antiretroviral therapy which may lead to death. This was the reason that genotyping has become a very important in routine diagnosis and management of chronic viral hepatitis infections. The purpose of this study was to see HCV genotypes among Libyan patients by LiPA technique, were a 75 blood samples were collected and processed at the laboratory of BIDIC (Benghazi Center of Infectious disease and Immunity) to perform the viral load and HCV genotyping. It was found that (60 %) of the collected samples belongs to HCV genotype 4, and (26.7 %) subtype 1a, while other subtypes 2a/2c, subtype 1b; Subtype 1a /1b; and genotype 2 all represented 5.3%; 5.3 %; 1.3 %; 1.3 % respectively. This concluded that HCVgenotypes in libya is distributed consuistently with Libyan neighboring countries. And the analysis of the 5′ UTR by LiPA with the INNO-LiPA HCV II kit can provide a quick, simple and reliable method for determination of the HCV genotype.